Long-Term Disability Outcomes for Patients With Ischemic Stroke Presenting With Visual Deficits. Issue 4 (14th December 2022) - Johnson, Natalie; Nisar, Tariq; Criswell, Amber; McCane, David; Lee, Jason; Chiu, David; Gadhia, Rajan
Abstract : Background: Ischemic strokes in both the anterior and posterior circulation can lead to visual deficits, which can affect functional ability. Thrombolytic therapies are often withheld to patients with visual deficits because of either being missed on initial evaluation or because of the misconception that their deficits are not as severe or as disabling. Alternatively, delays in patient arrival for emergent evaluation lead to missed opportunities for acute stroke treatment. This retrospective study aims to explore the differences in perceived long-term disability for patients with stroke who present with visual deficits vs those who do not as a manifestation of their acute stroke syndrome. In addition, we explore the differences in treatment effect with thrombolytics and further analyze if the region of ischemia causing the deficit leads to differences in disability outcomes. Methods: We conducted a retrospective analysis of patients with visual deficits as evidenced by an abnormal score on NIHSS categories related to vision (gaze palsy, visual fields, or extinction/inattention). Patients with Acute Ischemic Stroke were reviewed from the Houston Methodist Hospital Outcomes-based Prospective Endpoints in Stroke (HOPES) Registry from 2016–2021 for visual deficits. In total, 155 patient charts with visual deficits and 155 patient charts without a documented visual deficit were reviewed for ischemic stroke location (anterior vs posterior circulation), NIHSS scores, and thrombolytic therapies. The outcome variable was categorized using mRS, as mRS between 0 and 3 while mRS 4 to 6 was considered as poor functional outcome at 90 days. The independent variable was the vision group. A multivariable logistic regression model was constructed adjusting for demographics and comorbidities on the binary outcome. Results: Multivariable logistic model after adjusting for demographics and comorbidities showed that patients with acute ischemic stroke with vision defects were 4 times more likely to have poor functional outcomes at 90 days, with most of these patients (14% vs 6%; P < 0.05) suffering from severe disability compared with patients in the control group (i.e., patients with acute ischemic stroke without vision defects) (OR = 4.05; 95% CI [2.28–7.19]; P < 0.001). The application of thrombolytics and the location of ischemia (ACS vs PCS) did not result in a significant change in disability outcomes in patients with visual defects in this limited sample size. Conclusions: The results of this study indicated that a large population of patients with ischemic stroke experience visual deficits and are, therefore, at an increased likelihood of worse functional outcome. This reveals the necessity for rehabilitation techniques that specifically target visual deficits to speed up the recovery process of these patients. Further studies with larger sample size are needed to assess whether the location of ischemic event and the application of thrombolytic treatments plays a role in the disability outcomes of these patients.